On the need for comparative study ofpublic administration and administrative law - Cendrowicz, Dominika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of this paper is to present the objectives of comparative method in the study of public administration and administrative law.
Keywords: culturalfactors; comparative public administration; comparative administrative law; comparative method